Updated survival analysis of a randomized phase III study of subcutaneous versus intravenous bortezomib in patients with relapsed multiple myeloma - Bertrand Arnulf; Halyna Pylypenko; Sebastian Grosicki; Ievgenii Karamanesht; Xavier Leleu; Helgi van de Velde; Huaibao Feng; Andrew Cakana; William Deraedt; Philippe Moreau (Haematologica, 2012)
The phase III MMY-3021 study compared safety and efficacy of subcutaneous versus intravenous administration of the proteasome inhibitor bortezomib in patients with relapsed myeloma. The initial report demonstrated non-inferior efficacy with subcutaneous versus intravenous bortezomib for the primary end point: overall response rate after four cycles of single-agent bortezomib. We report updated outcome analyses after prolonged follow up. Best response rate (after up to ten cycles of bortezomib ± dexamethasone) remained 52% in each arm, including 23% and 22% complete or near-complete responses with subcutaneous and intravenous bortezomib, respectively. Time to progression (median 9.7 vs. 9.6 months; hazard ratio 0.872, P=0.462), progression-free survival (median 9.3 vs. 8.4 months; hazard ratio 0.846, P=0.319), and overall survival (1-year: 76.4% vs. 78.0%, P=0.788) were comparable with subcutaneous versus intravenous bortezomib. Peripheral neuropathy rates remained significantly lower with subcutaneous versus intravenous bortezomib, with increased rates of improvement/resolution at the time of this analysis.